PARADIGMA TRADISIONALIS DALAM PEMIKIRAN POLITIK ISLAM MODERN - Efi Syarifudin (Al Qalam, 2006)
As a traditionalist political thinker in modern era, Rasyid Ridha (1865-1935) had shown a relation between caliphate system and modern Islamic state system. He tried to formulate ''tradition" to answer political problem in modern era. Until the value of civil authority and humanized law included/formulated in Islamic state model which draft by him. He believed that the caliphate system could unify Islamic society in one leadership.An idea drafted by Ridha about ahl hal wal aqd institution and caliphate was more thrive than the thinkers before (classical thinkers), especially on competency, characteristic and the duties of caliphate and ahl hal wal aqd. A number of Ridho's idea had repeated classical thinker's thought, but Ridha able to modify it with the social reality. Ridha had made effort to set his ideas with writing activities and political movement to maintain caliphate tradition in Islamic state.